Vocabulary-Based Computer Assisted Language Learning (CALL) - Irani Z, Ulfah; Maulana, Riyan (Lembaga KITA, 2024)
This research aims to explore the implementation of Computer-Assisted Language Learning (CALL) in vocabulary instruction and its impact on students' vocabulary proficiency. The study employs a descriptive qualitative research design, utilizing purposive sampling to select participants. Data collection methods included questionnaires, observations, and documentary analysis to gather comprehensive insights into the effectiveness of CALL in the classroom. The findings reveal that CALL significantly enhances student achievement, with 86% of the students scoring within the excellent to good range in vocabulary assessments. The integration of computers in the learning process has been shown to positively influence vocabulary acquisition, making it a valuable tool in language education. Additionally, the use of CALL has been found to increase student motivation. The interactive elements provided by CALL, such as sounds, images, animations, and colors, contribute to making the learning experience more engaging and appealing for young learners. Consequently, CALL emerges as an effective method for both improving vocabulary skills and enhancing student engagement in language learning.